SELF-ASSESSMENT AND REFLECTION IN PORTFOLIOS ENHANCING EFL STUDENTS’ WRITING - Tengku Silvana Sinar; Liza Amalia Putri; Dian Marisha Putri (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2019)
ABSTRACTCan self-assessment and reflection as a part of the writing process make EFL students enhance their writing? This article presents the findings of a semester-long study conducted at four universities in Medan, North Sumatera where writing portfolio including self-assessment and reflection practices were implemented to support students make their progress. Using pre- and post- test design, it was found that the writing performance of students who used portfolio mainly focusing on combination of self-assessment and reflection for their essay writing process over a semester more increased than students who did not. The growth of writing performance corresponded to students’ ideas of improvement in writing. EFL writers who were usually concerned with correcting surface-level errors (mechanics and vocabulary) rather than global errors (organization and content), in this study, partially focused on global errors. Keyword: self-assessment, EFL students